Finite Element Analysis of CNT Reinforced Epoxy Composite Due to Thermo-mechanical Loading. (2016) - Singh, Anuj Kumar; Harsha, S.P.; Parashar, A.
Abstract: A Finite Element analysis of carbon nanotube (CNT) reinforced Epoxy based composite subjected to thermo-mechanical loading is presented in this paper. A coupled field analysis of a hexagonal RVE with long and short CNT embedded in an epoxy polymer matrix is carried out to analyze the effect of CNT reinforcement on the thermo-mechanical properties of the epoxy polymer. The analysis shows that long CNT's prove to be better reinforcement than short CNT's for the nano composites subjected to thermo-mechanical loading